Service Sweethearting: Its Antecedents and Customer Consequences - Brady, Michael K.; Voorhees, Clay M.; Brusco, Michael J. (Journal of Marketing, 2012)
This research is the first to examine service sweethearting, an illicit behavior that costs firms billions of dollars annually in lost revenues. Sweethearting occurs when frontline workers give unauthorized free or discounted goods and services to customer conspirators. The authors gather dyadic data from 171 service employees and 610 of their customers. The results from the employee data reveal that a variety of job, social, and remuneration factors motivate sweethearting behavior and several measurable employee traits suppress its frequency. The results from the customer data indicate that although sweethearting inflates a firm's satisfaction, loyalty, and positive word-of-mouth scores by as much as 9%, satisfaction with the confederate employee fully mediates these effects. Thus, any benefits for customer satisfaction or loyalty initiatives are tied to a frontline worker that the firm would rather not employ. Marketing managers can use this study to recognize job applicants or company settings that are particularly prone to sweethearting and as the basis for mitigating a positive bias in key customer metrics.